2015
DOI: 10.1111/ijfs.12809
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of red bean protein [Vigna angularis] isolate on rheological properties of pork myofibrillar protein gels induced by microbial transglutaminase

Abstract: Summary The effects of 1% red bean protein isolate (RBPI) on the gel properties of myofibrillar protein (MP) in various levels of microbial transglutaminase (MTG: 0%, 0.1%, 0.5%, & 1%) were evaluated. The cooking yield (CY) of the MP gels decreased with increasing MTG level, while the addition of RBPI improved the CY of the MP gels. Gel strength (GS) was also improved when RBPI was incorporated into the MP gels containing higher than 0.5% of MTG. The addition of MTG and RBPI was slightly changed the endothermi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…The rigidity of a protein gel is determined by the amount of particles (aggregates) incorporated into the gel network and the strength of the interactions between these particles (Jiang & Xiong, ). Although l ‐His induced high amount of elastic aggregates with increased G′ value, the lack of disulphide bonding and compact protein cross‐linking that stabilised gel net work as we discussed in section 3.2 might lead to weak gel strength of MPs gel in low ionic strength (Jang et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The rigidity of a protein gel is determined by the amount of particles (aggregates) incorporated into the gel network and the strength of the interactions between these particles (Jiang & Xiong, ). Although l ‐His induced high amount of elastic aggregates with increased G′ value, the lack of disulphide bonding and compact protein cross‐linking that stabilised gel net work as we discussed in section 3.2 might lead to weak gel strength of MPs gel in low ionic strength (Jang et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…. On the other hand, the corresponding changes of MP gel strength could be explained by the three‐dimensional structures of MPs (Chen et al ., ; Jang et al ., ). Low strength demonstrated in MPs gel in 1 m m NaCl containing l ‐His (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…A previous study described the high protein solubility and emulsion stability of red bean protein isolate (RBPI) at various pHs ( Meng and Ma, 2002a ). In our previous study, RBPI improve the gelling properties and cooking yield of meat protein gels mediated by MTG, which could improve the textural and functional properties of meat proteins as a potential water and meat binder ( Jang and Chin, 2011 ; Jang et al , 2015 ), which could improve the textural properties of meat products ( Hong and Chin, 2010 ). In our previous study, Jang et al (2015) reported that the optimum condition was 1% RBPI induced with 1% MTG.…”
Section: Introductionmentioning
confidence: 99%
“…Other main areas of research were the potential utilisation of food waste streams/by‐products as added value ingredients (Jang et al ., ; Peng et al ., ; Riedel et al ., ; Rocha Parra et al ., ; Lu et al ., ; Lucas‐González et al ., ; Teixeira et al ., ; Wu et al ., ) and novel food‐processing technologies (de Carvalho Rodrigues et al ., ; Shi & Maleky, ; Juodeikiene et al ., ; Xue et al ., ; Wang et al ., ).…”
mentioning
confidence: 99%